OPTIMASI SINTESIS ALUMINIUM FORMAT-METAL ORGANIC FRAMEWORK MENGGUNAKAN METODE PERMUKAAN RESPON - Faris Achmad Parmadi; Nikmah Nurjannah; Muhammad Ardycha Yudha Ramadhani; Amalia Wulandari; Anjasmoro; Zainal Arifin, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This research aims to optimize the synthesis of Aluminium Formate-Metal Organic Framework from beverage can waste as a carbon absorbing material using the response surface methodology. Two-level and two-factor Central Composite Design was used to determine the effect of the Al/HCOOH mole ratio (1:3-1:7) and reaction time (1-3 hours) on the yield value of the ALF-MOF product obtained. With this design, 13 experimental data were obtained. ALF-MOF synthesis was carried out via the solvothermal method. The ALF-MOF synthesis process is carried out by mixing Al(OH)3 powder obtained from aluminum extraction in beverage can waste and HCOOH in DMF. The mixture was stirred and heated in an autoclave reactor at 100oC with the reaction time according to the experimental design. The solid formed is filtered, washed and dried. The final product obtained was characterized using FTIR. Based on regression analysis, it shows that the experimental data fits the quadratic equation model with a coefficient of determination (R2) value of 0.7150 and an F model value of 677.68. Optimum conditions were achieved at the Al/HCOOH mole ratio and reaction time of 1:3,729 and 2,874 hours respectively with an ALF-MOF yield value of 87.71%. The percentage error in model verification data is 0.50%, which means that the level of validity of the data obtained reaches 99.50%.